Effective excitons separation on graphene supported ZrO2TiO2 heterojunction for enhanced H2 production under solar light. (22nd February 2018) - Subha, N.; Mahalakshmi, M.; Myilsamy, M.; Lakshmana Reddy, N.; Shankar, M.V.; Neppolian, B.; Murugesan, V.
Abstract: A novel photocatalyst comprises of ZrO2 TiO2 immobilized on reduced graphene oxide (rGO) – a ternary heterojunction (ZrO2 TiO2 /rGO) was synthesized by using facile chemical method. The nanocomposite was prepared with a strategy to achieve better utilization of excitons for catalytic reactions by channelizing from metal oxide surfaces to rGO support. TEM and XRD analysis results revealed the heterojunction formed between ZrO2 and single crystalline anatase TiO2 . The mesoporous structure of ZrO2 TiO2 was confirmed using BET analysis. The red shift in absorption edge position of ZrO2 TiO2 /rGO photocatalyst was characterized by using diffuse reflectance UV–Visible spectra. ZrO2 TiO2 /rGO showed greater interfacial charge transfer efficiency than ZrO2 TiO2, which was evidenced by well suppressed PL intensity and high photocurrent of ZrO2 TiO2 /rGO. The suitable band gap of 1.0 wt% ZrO2 TiO2 /rGO facilitated the utilization of solar light in a wide range by responding to the light of energy equal to as well as greater than 2.95 eV by the additional formation of excited high-energy electrons (HEEs). ZrO2 TiO2 /rGO showed the enhanced H2 production than TiO2 /rGO, which revealed the role of ZrO2 for the effective charge separation at the heterojunction and the solar light response. The optimum loading of 1.0 wt% of ZrO2 and rGO on TiO2 showed the highest photocatalytic performance (7773 μmolh −1 g c a t − 1 ) for hydrogen (H2 ) production under direct solar light irradiation. Highlights: ZrO2 TiO2 /rGO nanocomposites were prepared by using hydrothermal method. ZrO2 TiO2 heterojunction on rGO suppressed the e − -h + recombination and improved the H2 production. The photocatalytic H2 production was enhanced by the high energy electrons.